Vacancy defect engineering in semiconductors for solar light‐driven environmental remediation and sustainable energy production. Issue 2 (28th April 2022) - Ding, Yang; Maitra, Soumyajit; Wang, Chunhua; Halder, Somoprova; Zheng, Runtian; Barakat, Tarek; Roy, Subhasis; Chen, Li‐Hua; Su, Bao‐Lian
Abstract: The introduction of vacancy defects in semiconductors has been proven to be a highly effective approach to improve their photocatalytic activity owing to their advantages of promoting light absorption, facilitating photogenerated carrier separation, optimizing electronic structure, and enabling the production of reactive radicals. Herein, we outline the state‐of‐the‐art vacancy‐engineered photocatalysts in various applications and reveal how the vacancies influence photocatalytic performance. Specifically, the types of vacancy defects, the methods for tailoring vacancies, the advanced characterization techniques, the categories of photocatalysts with vacancy defects, and the corresponding photocatalytic behaviors are presented. Meanwhile, the methods of vacancies creation and the related photocatalytic performance are correlated, which can be very useful to guide the readers to quickly obtain in‐depth knowledge and to have a good idea about the selection of defect engineering methods. The precise characterization of vacancy defects is highly challenging. This review describes the accurate use of a series of characterization techniques with detailed comments and suggestions. This represents the uniqueness of this comprehensive review. The challenges and development prospects in engineering photocatalysts with vacancy defects for practical applications are discussed to provide a promising research direction in this field. Abstract : The state‐of‐the‐art vacancy‐engineered photocatalysts in various applications and the effects of vacancies on photocatalytic performance have been outlined. The types of vacancy defects, the methods for tailoring vacancies, the advanced characterization techniques, the categories of photocatalysts with vacancy defects, and the corresponding photocatalytic behaviors are presented.